(untitled) (Journal of the College of Basic Education, 2022)
With the emergence of human gatherings and the multiplicity of forms of interaction between individuals and societies, the complexity of life Social Individuals, social groups, and societies have begun to establish specific standards for regulating images Multiple social interactions and dealings, which have transformed over time from mere naive standards to others There are serious and binding standards that all members of society must abide by in their daily behavior In order to guarantee the rights of others and thus achieve a kind of social cohesion,